الكشف عن حالات الإصابة بفيروس الهربس النطاقي وعلاقته بالجنس: دراسة ميدانية داخل بعض عيادات الجلدية بمدينتي العجيلات وصبراتة - نجاح مديهين; نجلاء مصطفى السائح (Surman Journal of Science and Technology, 2025)
This study aims to detect cases of herpes zoster (shingles) infection among the study sample based on diagnostic tests. It also aims to determine the prevalence of herpes zoster within the sample, analyze the relationship between herpes zoster infection and sex (male/female), and compare males and females in terms of the pattern and severity of herpes zoster infection, if the necessary clinical data are available. The study included 28 patients with herpes zoster (shingles), ranging in age from under 20 to over 70 years old, who were patients at the dermatology clinics of the dermatology departments in the studied centers and were diagnosed with this disease. All participants were interviewed and clinically examined by dermatologists, and data was then collected using specially designed questionnaires after obtaining their informed consent. The questionnaire consisted of seven sections: six for the patients and one for the six participating physicians. The study concluded that females are more likely to be infected with the herpes zoster virus than males, with females comprising 64% of the sample compared to 36% for males. It also revealed that older age groups are more susceptible, with the highest incidence recorded in the 60–69 age group. Furthermore, the study found that the majority of those infected suffered from chronic diseases, suggesting a possible link between chronic illnesses and an increased risk of shingles infection. The results confirmed that all cases were medically diagnosed, enhancing the reliability of the data and the accuracy of the findings. The study also indicated that a painful rash and pre-inflammatory pain or tingling is among the most prominent clinical symptoms of shingles infection.